STRATEGIES FOR TEACHER ADAPTATION TO TECHNOLOGICAL CHALLENGES AND THE INTEGRATION OF ICT IN EDUCATION - Leidy Judith Lazo Ojeda; Cecilia Calderón Trujillo (LÍNEA IMAGINARIA, 2025)
The integration of Information and Communication Technologies (ICT) in education presents a significant challenge for teachers, who must adapt to a new digitalized reality. This article examines teacher adaptation strategies in response to technological challenges and the integration of ICT into educational processes, a topic that has gained prominence amidst the rapid transformation of learning environments. The study draws on the ideas of Andrés Oppenheimer, Francisco Mora, and Edgar Morin, who, from different perspectives, emphasize the importance of transforming education to address the challenges of the 21st century. Oppenheimer highlights the need to innovate pedagogical methodologies to effectively leverage ICT, while Mora stresses the importance of neuroeducation and the need to consider emotional and cognitive processes in teaching. Morin, on the other hand, advocates for an integrative approach that allows for the construction of critical and ethical knowledge suited to the challenges of the digital world. The findings of this study indicate that the main barriers to ICT integration include the lack of ongoing teacher training and inadequate infrastructure. However, it is concluded that overcoming these barriers requires a profound shift in teachers’ mindset, curriculum updates, and the implementation of educational policies that promote inclusive, dynamic, and flexible teaching. Ultimately, the successful integration of ICT will depend on institutional commitment and continuous teacher training to ensure equitable and quality learning.